Autocrine androgen action is essential for Leydig cell maturation and function, and protects against late‐onset Leydig cell apoptosis in both mice and men. Issue 3 (17th November 2014) - O'Hara, Laura; McInnes, Kerry; Simitsidellis, Ioannis; Morgan, Stephanie; Atanassova, Nina; Slowikowska‐Hilczer, Jolanta; Kula, Krzysztof; Szarras‐Czapnik, Maria; Milne, Laura; Mitchell, Rod T.; Smith, Lee B.
Abstract : Leydig cell number and function decline as men age, and low testosterone is associated with all "Western" cardio‐metabolic disorders. However, whether perturbed androgen action within the adult Leydig cell lineage predisposes individuals to this late‐onset degeneration remains unknown. To address this, we generated a novel mouse model in which androgen receptor (AR) is ablated from ~75% of adult Leydig stem cell/cell progenitors, from fetal life onward (Leydig cell AR knockout mice), permitting interrogation of the specific roles of autocrine Leydig cell AR signaling through comparison to adjacent AR‐retaining Leydig cells, testes from littermate controls, and to human testes, including from patients with complete androgen insensitivity syndrome (CAIS). This revealed that autocrine AR signaling is dispensable for the attainment of final Leydig cell number but is essential for Leydig cell maturation and regulation of steroidogenic enzymes in adulthood. Furthermore, these studies reveal that autocrine AR signaling in Leydig cells protects against late‐onset degeneration of the seminiferous epithelium in mice and inhibits Leydig cell apoptosis in both adult mice and patients with CAIS, possibly via opposing aberrant estrogen signaling. We conclude that autocrine androgen action within Leydig cells is essential for the lifelong support of spermatogenesis and the development and lifelong health of Leydig cells.—O'Hara, L., McInnes, K., Simitsidellis, I., Morgan, S., Atanassova, N., Slowikowska‐Hilczer, J., Kula, K., Szarras‐Czapnik, M., Milne, L., Mitchell, R. T., Smith, L. B., Autocrine androgen action is essential for Leydig cell maturation and function, and protects against late‐onset Leydig cell apoptosis in both mice andmen. FASEB J. 29, 894–910 (2015). www.fasebj.org